2019
DOI: 10.26603/ijspt20190459
|View full text |Cite
|
Sign up to set email alerts
|

CLINICAL RELEVANCE of the LIGAMENTUM TERES: A LITERATURE REVIEW

Abstract: Background: The ligamentum teres (LT) continues to be a structure of debate and interest. Previously thought of as a vestigial structure, an awareness of LT pathology and its potential importance has increased with the expansion of hip arthroscopy. Purpose: To provide a comprehensive literature synthesis on the LT and provide clinicians with the most current research regarding the LT and its anatomical features, functional relevance, prevalence of injury, risk factors for injury, clinical presentation, and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…The reported prevalence of LT pathology (including synovitis, partial and complete tears) found during HA surgery varies from 4% to 93% [ 3 , 19 ]. According to Haviv and O’Donnell, an LT tear is observed in 9% of the patients who undergo HA [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported prevalence of LT pathology (including synovitis, partial and complete tears) found during HA surgery varies from 4% to 93% [ 3 , 19 ]. According to Haviv and O’Donnell, an LT tear is observed in 9% of the patients who undergo HA [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the function of the ligamentum teres (LT) were first published in the 19th century [ 1 ]. With the development of hip arthroscopy (HA) in recent decades, interest in and the importance of the function and role of the LT has been gradually emphasized [ 2 , 3 ]. Leunig et al .…”
Section: Introductionmentioning
confidence: 99%
“…The function of the Ligamentum teres (LT) has not been fully clarified to date. According to recent studies, it restricts external rotation and flexion in the hip joint, where it acts as a final stabilizer [8] [9] [10]. Additionally, the LT seems to have mechanoreceptors which help to counter micro instability by activating muscular stabilizers of the hip joint [11].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, chronic instability, such as dysplasia or femoroacetabular impingement (FAI) with hypomochlion effect, can lead to recurrent overstretching of the LT and concomitant lesions [12]. This can also be caused by certain sports where a large range of motion is required [10].…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 18 , 19 , 20 , 21 Moreover, the prevalence of complete LT tears has been reported to range from 1% to 26%, 1 , 7 , 13 , 14 , 15 , 19 , 22 with complete tears being more common in patients with greater severity of bony deformity. 17 , 23 Studies to date have rarely found LT tears to occur in isolation and have instead suggested LT tears to represent an end-stage consequence of pathomechanical changes occurring within the hip due to concurrent bony and soft-tissue pathology. 6 , 7 , 17 , 24 …”
mentioning
confidence: 99%